Problem Based Learning (PBL) Learning Model and Impact on Students' Critical Thinking Skills in Mathematics Learning - Munawaro, Fadillatul; Mawardi, Dona Ningrum; Friansah, Drajat (Global Education Journal, 2025)
Education is a basic need for human beings today the world of education is expected to be challenged to be able to produce individuals who can meet global demands. This study aims to describe students' critical thinking skills in mathematics learning with the Problem Based Learning model. The method used in this study is the SRL (Systematic Literatul Review) method. SRL is carried out by the researcher by identifying, reviewing, evaluating and interpreting all available research. The results of the study show that the Problem Based Learning learning model used can hone students' critical thinking skills, after using the Problem Based Learning learning model, students can have diverse critical thinking skills. The positive impact of PBL on students' critical thinking skills includes improving the ability to identify problems, collect and analyze information, and formulate appropriate solutions. In addition, PBL can also increase students' motivation to learn and promote collaboration and communication skills in the context of mathematics learning.